PEMBENTUKAN KARAKTER: AKTUALISASI PENDIDIKAN KARAKTER DI KELUARGA, SEKOLAH, DAN MASYARAKAT - Lenggono, Wahyu (Penerbit CV Tentrem Karya Nusa, 2019)
This article discusses character building (actualization of character formation in families, school institutions, and community environments. This research is a qualitative study using library methods or library research, the authors explain the actualization of character formation in families, school institutions, and the community through a community words (descriptive) based on information or data obtained from books and journals that exist.In addition, this paper is intended to know correctly and deeply about the actualization of the formation of human character in the three components of the implementation of education, so that readers have a good knowledge of the topic being studied in this article.Based on the study conducted by the author it can be stated that character formation is an effort carried out through the educational process, namely through guidance, teaching, practice, practice, and habits. n to students, that is to form students with noble values and practice Islamic values in their lives. Actualization of character formation can be done through three components that are very vital in human life, namely in the family, school institution, and community environment.Key Words: Character formation, family, school, community